'Excessive drinking - An inescapable part of university life?' A focus group study of Australian undergraduates - Hallett, Jonathan; McManus, Alexandra; Maycock, Bruce; Smith, Jennifer; Howat, Peter (Scientific Research Publishing, 2014)
The university environment reinforces positive alcohol-related expectations and motivations for drinking among undergraduate students. High levels of hazardous consumption in this population lead to significant negative alcohol-related consequences, for individuals and those around them. This study sought to explore the contexts in which those who engage in hazardous drinking consume alcohol, their perceptions of safety and harm, and receptivity to health messages. Undergraduate university students (n = 69; aged 17 - 24 of both genders [57% female]) were purposively recruited into one of seven focus groups after screening with the Alcohol Use Disorders Identification Test (AUDIT) to select for hazardous drinking (score, >8) or moderate drinking. A focus group interview schedule was developed, which was informed by theory and tested for validity by a panel of experts.Qualitative analysis of the data revealed four thematic clusters: positive expectations; inescapable culture; defining situations; and permissible drunkenness. Drinking was associated with various personal and social advantages that reinforced participants’ intentions and/or willingness to drink. Alcohol played a meaningful role in the way in which participants identified with youth and university culture. Economical drinking was prominent, with students constantly negotiating pathways to intoxication within the confines of their budgets. Heavy drinking was viewed as permissible when in the home environment and/or in the company of trusted friends. Most students were unreceptive to health messages, and advice on restricting alcohol consumption seemed to have limited impact on drinking behaviour. Our findings clarify why some university students maintain or increase drinking behaviour despite known negative out- comes and offer useful insights to inform further research and the development of alcohol interventions specifically targeted at students.